2011
DOI: 10.1136/jclinpath-2011-200265
|View full text |Cite
|
Sign up to set email alerts
|

HER2genetic heterogeneity in breast carcinoma

Abstract: HER2 genetic heterogeneity according to the ASCO/CAP definition is frequent in breast carcinoma, and is most often present in carcinomas with an equivocal (2+) HER2 score. Many carcinomas with HER2 genetic heterogeneity have a negative HER2 amplification status, although they contain a significant number of tumour cells with HER2 gene amplification. Single cell scoring of the HER2/17 centromeric probe (CEP17) ratio is necessary to identify carcinomas with HER2 genetic heterogeneity, because they lack specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 21 publications
3
48
0
1
Order By: Relevance
“…Of note, HER2 heterogeneity was also frequently observed in cases with mean CEP17 copy numbers .3 (approximately 37%), as reported previously [13]. In diagnostic terms, this association may lead exponentially to troublesome interpretation of ISH results.…”
Section: Discussionsupporting
confidence: 72%
“…Of note, HER2 heterogeneity was also frequently observed in cases with mean CEP17 copy numbers .3 (approximately 37%), as reported previously [13]. In diagnostic terms, this association may lead exponentially to troublesome interpretation of ISH results.…”
Section: Discussionsupporting
confidence: 72%
“…However, these same authors found that HER2 genetic heterogeneity according to the ASCO/CAP definition is most often present in breast carcinomas with an equivocal (2 þ ) HER2 score. 26 This correlates with our observation that patients who received an equivocal (2 þ ) HER2 score also tended to have the highest heterogeneity as well.…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, if 60 cells are examined and 3 or more cells have a ratio higher than 2.2, HER2 GH is present." Using this definition leads to substantially higher rates of HER2 heterogeneity by FISH ranging from 14% to 26% in breast cancers (47,48). However, use of the same definition in gastric cardia, GEJ, and esophagus adenocarcinomas demonstrated only 20 of 675 (2.9%) have HER2 genetic heterogeneity (42).…”
Section: Her2 Genomic Heterogeneitymentioning
confidence: 99%